x^3 - x = x(x^2 - 1) = (x) (x+1) (x-1) - this is difference of two squares.
3c^4 - 81c = we can factor a 3c from the the term, getting:
3c(c^3-27) Now, for the inner part you can use the (x-y) term, and finish with:
(3c) (c-3) (c^2 +3c +9)
Top one:
X^3 +Y^3 is d^6+h^3 So X is d^2, and Y is h
(d^2+h) (d^4 -d^2h + h^2)
Factor out whatever lower terms you can first, to get it into a difference of two squares, or difference of two cubes, then follow the rules.
2006-12-18 17:38:53
·
answer #1
·
answered by John T 6
·
0⤊
0⤋
d^6 + h^3 = (d^2)^3 + h^3
from hereon you can use the formula for the sum of 2 cubes.
3c^4 - 81c = 3c*(c^3 - 9) = 3c*(c^3 - 3^3)
from hereon you can use the formula for the diference of 2 cubes for the terms in the parenthesis
x^3 - x = x*(x^2 - 1)
ok something is wrong here. Either the equation is x^4 - x or you are supposed to use the formula for the difference between 2 squares.
2006-12-19 04:15:19
·
answer #2
·
answered by dkrudge 2
·
0⤊
0⤋
ok these are great fun. first of all your formula for getting the answer is F^3 + S^3 = (F+S)(F^2 - FS + S^2) or
F^3 - S^3 = (F- S)(F^2+ FS + S^2)
F= the first number
S= the second number
so #1, d^6 + h^3 = (d^2)^3 + (h)^3
F= d^2 and S= h^3
(d^2 + h^3)(d^4 - d^2h^3 + h^6) is your answer
#2, 3c^4 - 81c= 3c(c^3 - 27) = 3c(c^3 - 3^3)= 3c[ (c)^3 - (3)^3]
F=c
S=3 note: after factoring F and S, you must multiply the
answer by 3c
3c(c-3)(c^2 + 3c + 9) is your answer
plz vote mine best
2006-12-19 01:42:41
·
answer #3
·
answered by Anonymous 2
·
0⤊
0⤋
d^6 + h^3 = (d^2)^3 + h^3 = (d + h)(d^2 - dh + h^2)
3c^4 - 81c = 3c (c^3 - 27) = 3c (c^3 - 3^3) = 3c (c - 3)(c^2 + 3c + 9)
x^3 - x = x (x^2 - 1) = x (x +1)(x - 1)
Lat one can't be written in the form of a^3 - b^3 unless we are ready to take Cube root of x as one term .
2006-12-19 01:38:29
·
answer #4
·
answered by Srinivas c 2
·
0⤊
0⤋
d^6 + h^3 These terms have nothing in common with each other and therefore has no factors that I can see.
3c^4 - 81c
3c(c^3-21)
x^3 - x
x(x^2-1)
2006-12-19 01:35:37
·
answer #5
·
answered by Tony T 4
·
0⤊
0⤋
d^6 + h^3 =
(d^2 + h)(d^4 -d^2h + h^2)
3c^4 - 81c =
3c(c^3 - 27) =
3c(c - 3)(c^2 +3c + 9)
x^3 - x =
x(x^2 - 1) =
x(x - 1)(x + 1)
2006-12-19 01:43:40
·
answer #6
·
answered by Helmut 7
·
0⤊
0⤋
you need to get help from your school. getting your homework done here is cheating, and it won't help you, as you'll never learn. Get help from your school.
2006-12-19 01:41:15
·
answer #7
·
answered by Rick 5
·
0⤊
0⤋